2019
DOI: 10.1521/pedi_2018_32_346
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder: Associations Between Dimensional Personality Profiles and Self-Destructive Behaviors

Abstract: Ongoing research is shifting towards a dimensional understanding of borderline personality disorder (BPD). Aim of this study was to identify personality profiles in BPD that are predictive of self-destructive behaviors. Personality traits were assessed (n = 130) according to the five-factor model of personality (i.e., Neuroticism, Extraversion, Openness to Experience, Agreeableness, Conscientiousness) and an additional factor called Risk Preference. Self-destructive behavior parameters such as non-suicidal sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Our sample is consistent with other clinical samples, characterized by high scores on N and low on all other traits (20,21). When comparing between the categorically defined groups, we observed significant differences in N and E between these two groups, with less extreme scores on BDII.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our sample is consistent with other clinical samples, characterized by high scores on N and low on all other traits (20,21). When comparing between the categorically defined groups, we observed significant differences in N and E between these two groups, with less extreme scores on BDII.…”
Section: Discussionsupporting
confidence: 89%
“…However, the literature considering clinical samples is less abundant, and recent evidence suggests that results from community samples cannot be readily translated to clinical settings. In fact, a study ( 20 ) found that non-suicidal self-injury and impulsive behaviors in BPD patients were predicted by higher levels of N, E, A, and C. As the authors hint, this apparently counter-intuitive finding may be mediated by other characteristics of BDP functioning, like emotional regulation, stress coping mechanisms, and interpersonal problems. Personality traits appear not to exert a direct effect but interact with the disorder core symptoms to modify the clinical outcome.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, sex hormones and pubertal timing could be involved in the pathophysiology of these disorders through the modulation of the neuroendocrine system. Moreover, sex-specific hormonal differences in estrogentestosterone ratio, variability in the timing of physical development and changes associated with menarche and menstruation could also represent possible biological mechanisms involved, explaining the gender difference found in NSSI behavior [33][34][35][36]. Structural and functional brain alterations could also represent a possible neurobiological key vulnerability in developing maladaptive coping strategies in adolescents.…”
Section: Socio-demographic and Clinical Features Of The Samplementioning
confidence: 99%
“…Hennings argues that suicide can be a way of suppressing emotions and the final effort to control psychological pain (18). Determining individual characteristics in patients may help us understand self-destructive behaviors in BPD more completely and to address them in diagnostic and therapeutic sessions more carefully (19). Most studies on the individual factors of suicidal behaviors have been performed quantitatively; however, it is not yet clear what dimensions predominate in the relationship between BPD and SAs.…”
Section: Introductionmentioning
confidence: 99%